Pengaruh Methanol Terhadap Torsi, Daya Epektif Dan Komsumsi Bahan Bakar Spesifik Epektif Pada Mesin Daihatsu Ferosa 1994 - Adi Sayoga, I Made (Universitas Mataram, 2012)
The research of the effect of methanol to the Torque, power effective and specific fuel consumption effective at Daihatsu Ferosa machine 1994 had been done. The research had done in mechanical engineering laboratory, engineering faculty mataram University. The percentage of methanol and premium was varied each 0%, 5%, 10%,15%and 20% methanol. Each fuel was tested at wide open throttle (WOT) at fourth transmission 1600rpm, 2100 rpm, 2600 rpm and 3600 rpm. The data that got in the experiment was analysis and calculated to find torque, effective power and specific fuel consumption effective. The result shown that at the higher percentage of methanol torque and power effective decrease gradually. Therefore the specific fuel consumption effective increase at the higher percentage of methanol.